1991
DOI: 10.1901/jeab.1991.56-261
|View full text |Cite
|
Sign up to set email alerts
|

Cocaine and Food as Reinforcers: Effects of Reinforcer Magnitude and Response Requirement Under Second‐order Fixed‐ratio and Progressive‐ratio Schedules

Abstract: Reinforcer magnitude and fixed-ratio requirement were varied under two second-order schedules. Under one, the first sequence of a fixed number of responses completed after the lapse of a 10-min fixed interval produced reinforcement. Under the second, a second-order progressive-ratio schedule, the fixed number of responses increased after each reinforcement. Either cocaine (0 to 300 micrograms/kg/inj) or food (0 to 5,700 mg/delivery) reinforcers were delivered. Under some conditions, a 2-s illumination of stimu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

1993
1993
2010
2010

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 40 publications
(36 citation statements)
references
References 19 publications
2
34
0
Order By: Relevance
“…The increased persistence of ethanol consumption in the presence of the ethanol-associated stimulus is similar to effects obtained with stimuli paired with cocaine infusions in second-order schedules of reinforcement (Spear and Katz 1991;Ranaldi and Roberts 1996). That is, cocaine-maintained responding persists at higher response requirements when these responses also intermittently produce stimuli paired with cocaine infusions.…”
Section: Discussionsupporting
confidence: 65%
“…The increased persistence of ethanol consumption in the presence of the ethanol-associated stimulus is similar to effects obtained with stimuli paired with cocaine infusions in second-order schedules of reinforcement (Spear and Katz 1991;Ranaldi and Roberts 1996). That is, cocaine-maintained responding persists at higher response requirements when these responses also intermittently produce stimuli paired with cocaine infusions.…”
Section: Discussionsupporting
confidence: 65%
“…Further, several of the experiments that have measured such performance have observed that the vehicle often maintains a breaking point substantially greater than zero (e.g. Gerber and Stretch 1975;Hoffmeister 1979;Spear and Katz 1991). Data from other reports indicate that the vehicle maintains little or no responding (e.g.…”
Section: Lack Of Assessments Of Vehicle-maintained Respondingmentioning
confidence: 99%
“…The response requirement at which responding ceases has been called the breaking point or breakpoint (BP). A variety of PR schedules have been used to study behavior maintained by several different positive reinforcers, including food (Spear and Katz 1991), sweetened solutions (Bedford et al 1978;Hodos 1961) and electrical stimulation of the brain (Hodos 1965;Keesey and Goldstein 1968). A general conclusion of those studies has been that BP increases with reinforcer magnitude.…”
Section: Introductionmentioning
confidence: 99%